1987
DOI: 10.1128/mcb.7.2.821
|View full text |Cite
|
Sign up to set email alerts
|

Different functional domains of the adenovirus E1A gene are involved in regulation of host cell cycle products.

Abstract: We have analyzed the ceH cycle effects that different domains of the adenovirus EIA proteins have on quiescent primary BRK cells. Studies with deletion mutants that in combination removed all but the N-terminal 85 amino acids common to both the 12S and 13S proteins suggest that this region may be sufficient for the induction of synthesis of proliferating cell nuclear antigen and the stimulation of DNA synthesis. A second domain also common to the N-terminal exon of the 12S and 13S proteins was required for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 77 publications
4
141
0
Order By: Relevance
“…We conclude that the 12S ElA gene product does possess transcription-inducing activity but that the efficiency of this activity depends on the target gene. The hsp7O gene may not be the only example of ElA-12S-mediated stimulation since it was recently shown that there is an increase in synthesis of the proliferating cell nuclear antigen in either 12S or 13S virus infection of primary baby rat kidney cells (59). Of potential interest is the fact that these two genes induced by the 12S ElA mutant (if indeed proliferating cell nuclear antigen gene induction is transcriptional) are also induced by an addition of serum to starved cultures.…”
Section: Simon Et Al In Preparation)mentioning
confidence: 99%
“…We conclude that the 12S ElA gene product does possess transcription-inducing activity but that the efficiency of this activity depends on the target gene. The hsp7O gene may not be the only example of ElA-12S-mediated stimulation since it was recently shown that there is an increase in synthesis of the proliferating cell nuclear antigen in either 12S or 13S virus infection of primary baby rat kidney cells (59). Of potential interest is the fact that these two genes induced by the 12S ElA mutant (if indeed proliferating cell nuclear antigen gene induction is transcriptional) are also induced by an addition of serum to starved cultures.…”
Section: Simon Et Al In Preparation)mentioning
confidence: 99%
“…The human papillomavirus E6 oncoprotein, which targets p53 for degradation, was found to attenuate mitotic delay in normal human ®broblasts only after an extended period of cell replication . Adenovirus E1A, another DNA tumor virus oncoprotein, can drive quiescent cells into both DNA replication and mitosis (Zerler et al, 1987). The domains of E1A required for these two functions are separable, implying that E1A interacts with cellular proteins that regulate entry into mitosis and that these proteins are distinct from those regulating entry into S phase.…”
Section: Introductionmentioning
confidence: 99%
“…The E1A CR2 domain is known to bind with the RB family of proteins, leading to immortalization of the primary culture cells and in cooperation with ras or E1B oncogenes, E1A can lead to transformation (Whyte et al, 1989;Corbeil and Branton, 1994). Deletion of the CR2 domain or even a site mutation to knock out the RB-binding site on E1A is su cient to abolish the immortalization function of E1A (Lillie et al, 1986;Moran et al, 1986;Zerler et al, , 1987Schneider et al, 1987;Kuppuswamy and Chinnadurai, 1987;Smith and Zi , 1988;Jelsma et al, 1989;Whyte et al, 1989). Thus, the deletion of the CR2 and CR3 domains in the mini-E1A would abolish the potential risk of immortalization and consequent transformation caused by wild type E1A.…”
Section: Discussionmentioning
confidence: 99%